Strengthening Legal Literacy among Vocational School Students Through Education on Personal Data and OJK-Licensed Online Loans - Ira Safitri; Reni Setiansyah; Anisa Safitri; Sulanda Sulanda; Permana Anggara; Dadang Sundawa; Dwi Iman Muthaqin (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to enhance students’ legal literacy regarding personal data protection and online lending services licensed by the Financial Services Authority (Otoritas Jasa Keuangan/OJK). The program was implemented through counseling sessions and interactive discussions involving 42 accounting students at SMK Muhammadiyah 2 Cibiru. Evaluation instruments consisted of pre-tests and post-tests, which were analyzed using descriptive quantitative and qualitative approaches. The results demonstrate significant improvements across all indicators of students’ legal understanding. The average normalized gain (N-Gain) scores were 0.33 (moderate category) for basic legal knowledge, 0.46 (moderate category) for legal attitudes and awareness, and 0.43 (moderate category) for higher-order thinking skills (HOTS). Overall, the findings indicate that legal education on personal data protection and financial literacy is effective in enhancing students’ awareness and critical thinking skills in addressing cybercrime risks in the digital era.